On the textual materiality, transmission and attribution of a fragment from the Aeschines Socraticus’ ’Alcibiades’ - de Oliveira Carvalhar, Carlos Augusto (Romanitas - Revista de Estudos Grecolatinos, 2023)
The aim of this paper is to demonstrate how diverse indications can be correlated in the attribution of a fragment to an author and work, using as example the Alcibiades of Aeschines of Sphetus, the Socratic. For this purpose the testimony present in Aelius Aristides will be addressed, where the paratextual annotations in his manuscripts indicate that it is a quotation, as well as there is a scholium that identifies the work and the author of this quotation, being it corroborated by an isolated phrase cited by Priscian and by the indication of Herodian and Choiroboskos, in addition to fragments of the Oxyrhynchus Papyri that present an indisputable textual similarity. Furthermore, a description of the transmission context of the Aristides’ manuscripts and their critical editions will be presented, as well as the modern and contemporary editions that collected the fragments of Aeschines, and the editorial aspects of these textual sources will be discussed.